Greening western China: A critical view - Yeh, Emily T. (Geoforum, 2009)
The dominant narrative in a growing literature about China’s environment conceptualizes a series of recent large-scale ecological construction projects, particularly in western China, as evidence of a teleological graduation into eco-rational modernity, in which environmental improvement and economic growth are intertwined in a virtuous, mutually reinforcing circle. Such ecological modernization narratives take for granted both a crisis of ecological degradation, and the premise that the “greening” of the state will have environmental improvement as its primary outcome. The article reviews recent research on ecological construction projects to protect forests and grasslands in China’s west, which have been identified as major components of China’s ecological modernization goals. It demonstrates the limitations of an ecological modernization framework for analyzing these projects, and argues instead for a critical political ecology analysis, which examines the distributive effects of these projects and employs an analytic of governmentality. Ecological construction is more productively understood as a set of discursive practices that authorize differential interventions through processes of internal territorialization, rework the relationship between different categories of citizens and the state, and produce subjects, whose desires may or may not align with those desired by state institutions.